PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 001 SINABOI - Rati, Ayu Rati Ayu; Antosa, Zariul Antosa Zariul; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is motivated by low mathematics learning outcomes of students, with an average grade of 49.6. While the completeness criteria Minimum value (KKM) Mathematics is 70 Among students, amounting to 24 people only 6 students who achieve KKM with classical completeness 25%. This research is Classroom Action Research (CAR) conducted aims to improve learning outcomes Mathematics Elementary School fourth grade students 001 Sinaboi by implementing STAD cooperative learning model. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results obtained by studying the average learning outcome measures 49.6 before rising 70.12% to 84.38 in cycle I. In the second cycle increased by 90.42% to an average of 94.45. activities of teachers in the first cycle the first meeting of the percentage of 65% obtained with enough categories, the second meeting had become 75%. Furthermore, the first meeting of the second cycle activity scores increased to 80% of teachers with excellent category, at the second meeting increased to 90% with very good category. The results of the data analysis of student activity in the first cycle to 60% with enough categories, at the second meeting 70% of the students already understand this cycle of learning activities with the implementation of STAD cooperative. And the second cycle students 75% activity score increased with both categories. At the second meeting increased to 85% with very good category. The results of the study in fourth grade Sinaboi 001 State prove that the implementation of STAD cooperative learning model to improve learning outcomes Math 001 fourth grade students of SDN Sinaboi. Keywords: Cooperative Type STAD, Matemathic leaning outcome